Electrocoiling-guided printing of multiscale architectures at single-wavelength resolution. Issue 11 (2nd May 2019) - Li, Jingmei; Kong, Tiantian; Yu, Jiazuo; Lee, Kit Hang; Tang, Yuk Heng; Kwok, Ka-Wai; Kim, Ji Tae; Shum, Ho Cheung
Abstract : An electrically assisted coiling-jet-based technique is introduced to print nanofibers with programmable patterns. Using this approach, we can swiftly switch filament patterns, enhancing the pattern resolution down to the micrometer range, representing a more than one hundred-fold improvement. Abstract : The rope coiling observed in liquid ink with high viscosity has been exploited in additive printing to fabricate architectures with periodically curled structures and tune their mechanical properties. However, the control over the coiling path relying on mechanical motion restricts the spatiotemporal resolution. We develop an electrically assisted high-resolution technique to manipulate coiling paths of viscous ink and structures of the deposited filament. By spatially programming the voltage applied onto the viscous ink, we show that the switching between different filament structures can be accomplished at single wavelength resolution, facilitating the rapid and accurate construction of sophisticated patterns. Furthermore, translational guiding of the electrocoiling enables rapid printing of filaments with complex structures at a line speed of 10 2 mm s −1 . With a simplified trajectory of the printing head, large-area and multiscale patterns can be printed at an unprecedented speed; for instance, centimeter-sized architectures constructed from nanofibers with micron-sized curled structures can be completed in a few minutes. By enabling the printing of complex fiber networks with tunable shape and density, our work provides a route towards custom-design of fiber architectures with unique features such as spatially varying mechanical properties.